A review of the hormones involved in the endocrine dysfunctions of polycystic ovary syndrome and their interactions - Emanuel, Rebecca H. K.; Roberts, Josh; Docherty, Paul D.; Lunt, Helen; Campbell, Rebecca E.; Möller, Knut (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) affects up to 20% of women but remains poorly understood. It is a heterogeneous condition with many potential comorbidities. This review offers an overview of the dysregulation of the reproductive and metabolic systems associated with PCOS. Review of the literature informed the development of a comprehensive summarizing ‘wiring’ diagram of PCOS-related features. This review provides a justification for each diagram aspect from the relevant academic literature, and explores the interactions between the hypothalamus, ovarian follicles, adipose tissue, reproductive hormones and other organ systems. The diagram will provide an efficient and useful tool for those researching and treating PCOS to understand the current state of knowledge on the complexity and variability of PCOS.